Application of Sludge-Based Adsorbent for Acid Red 18 Adsorption - PIECZYKOLAN Barbara (Architecture, Civil Engineering, Environment)
A study was conducted on the use of excess activated sludge from a municipal wastewater treatment plant as an adsorbent in the removal of Acid Red 18. The excess sludge was thermally modified using microwave radiation. The study aimed to evaluate the possibility of using this type of waste adsorbent in the batch adsorption process to remove a selected synthetic dye. Moreover, the experiments were aimed at analyzing the adsorption kinetics and adsorption isotherms of the batch adsorption process. Experimental results showed that in the case of adsorption kinetics, a greater match with experimental results was obtained for the pseudo-second-order model. This indicates that the adsorption process was chemical in nature. In the case of adsorption isotherm analysis, it showed that the best fit to experimental results was obtained for the Langmuir, Sips, and Toth isotherm models. Thus, this indicates the occurrence of a single-layer adsorption process. The determined values of adsorption capacity based on the Langmuir, Sips, and Toth models are in the range of 71.6 mg/g–79.0 mg/g.